2022
DOI: 10.1002/chem.202201145
|View full text |Cite
|
Sign up to set email alerts
|

The Coordination Chemistry of f‐Block Elements in Molten Salts

Abstract: The coordination chemistry of f-block elements (lanthanide and actinide) in molten salts has become a resounding topic in view of its great importance to the research and development (R&D) of molten salt reactors and pyroprocessing. In this Review article, a general overview of the coordination chemistry of f-block elements in molten salts is provided including past achievements and recent advances.Particular emphases are placed on the oxidation state, speciation, and solution structure of f-block metal ions i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 91 publications
0
4
0
Order By: Relevance
“…The x and y are the coordination number of Eu(II) and Eu(III) in diluent fluoride molten salts and equals to 4.5 ∼ 5.5 for x and 6 ∼ 8 for y in LiF or KF melt according to the coordination chemistry of rare Earth element in molten salts. 23 The first-principles molecular dynamic (FPMD) simulation results indicated that the x and y in FLiBe melt may be 7 for both Eu(II) and Eu(III), thus the Eq. 15 may be expressed more specifically as Eq.…”
Section: λ = [ ]mentioning
confidence: 99%
See 1 more Smart Citation
“…The x and y are the coordination number of Eu(II) and Eu(III) in diluent fluoride molten salts and equals to 4.5 ∼ 5.5 for x and 6 ∼ 8 for y in LiF or KF melt according to the coordination chemistry of rare Earth element in molten salts. 23 The first-principles molecular dynamic (FPMD) simulation results indicated that the x and y in FLiBe melt may be 7 for both Eu(II) and Eu(III), thus the Eq. 15 may be expressed more specifically as Eq.…”
Section: λ = [ ]mentioning
confidence: 99%
“…This phenomenon may be relevant to the different coordination sphere of the two species. 23 The linear fitting of lnD vs 1/T was performed for both ions (Fig. 7) according to the Arrhenius' law (Eq.…”
Section: Diffusion Coefficient Measured By Chronopotentiometry (Cp)mentioning
confidence: 99%
“…Versatility of speciation, which leads to formation of distinct complexes, drives targeted reactions that have contributed to the growth of coordination chemistry over recent years. 1,2 Different chemical functional groups, stereoisomers, or other structural features affect the coordination chemistry of product complexes by altering the speciation environment, including the steric and electronic characteristics of ligands. [3][4][5] Speciation of ionic liquids (ILs) is a good example that has attracted broad interest due to the unique molecular capabilities of ILs to trap targeted molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the behavior of molten salts is important for nuclear fuel reprocessing and the design of the advanced molten salt reactors (MSRs). To facilitate the development of the techniques in those areas, it is essential to understand the physical and chemical properties of f-elements in molten salts under different environmental conditions. , Of particular interest are the coordination number (CN) of anions around f-elements in solution, viscosity of the medium, and its thermal conductivity. These properties dictate the physical and chemical behavior of the solution such as diffusivity and the changes upon radioactive decay and transmutation of the fuel species…”
Section: Introductionmentioning
confidence: 99%